Inovasi Cemilan Kekinian Berbentuk Cheesecuit sebagai Makanan Penutup - Siti Aisyah; Muhammad Sinar Randi; Irda Wahyuni; Iis Rosidah; Juni Hati Hangoluan (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
The number of foods that are developing in the food sales industry. So that new innovations are needed both in terms of taste and packaging. Usually most people will eat dessert at the end of their meal. However, not infrequently many of us want to eat dessert eaten in our spare time or as we know when snacking. By using thinwall in various sizes, the author makes dessert food, namely cheesecake using thinwall to facilitate sales and consumption because the portion is right, meaning the portion is not excessive or not lacking at all. So in this writing this time we get to know the innovation of cheesecake snacks and how to make them which can be snacks in your spare time or become a sales idea for readers. The research method used is the literature review method and the method of opening a business. The literature review method itself comes from previous journals or books obtained by the author.